The Effect of Traditional Games on the Improvement of Gross Motor Skills Among Seventh Grade Students at PAB 8 Junior High School Sampali - Limbong, Irvan; Helmi, Boby (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study empirically investigates the effect of traditional games specifically Bentengan and Gobak Sodor on the improvement of gross motor skills among seventh-grade students at PAB 8 Junior High School Sampali in the 2023/2024 academic year. Employing a quasi-experimental design with a one-group pre-test and post-test model, the research involved 12 student participants. Data were collected using tests of arm power (medicine ball throw), running speed (20-meter sprint), and agility (4×5 meter shuttle run). Statistical analysis was conducted using a paired-sample t-test to determine the significance of the differences between pre-test and post-test results. The findings indicated significant improvements in all measured aspects of gross motor ability: arm power increased from 1.76 to 2.08, running speed improved from 6.16 seconds to 5.96 seconds, and agility improved from 16.52 seconds to 15.41 seconds. The t-test results showed that tcount > ttable for all variables, confirming a statistically significant effect. The study concludes that traditional games have a positive and significant impact on enhancing students’ gross motor skills, suggesting their potential integration into physical education programs as an effective, culturally rooted pedagogical tool.